PENGARUH NPF DAN FDR TERHADAP PROFITABILITAS (ROA) PADA UUS PT BANK SUMUT - Andhari, Diah Sepni; AK, Marlya Fatira; Kholil, Ahmad (Jurnal Budgeting, 2023)
This study is about "The Effect of NPF and FDR on Profitability (ROA) at the Sharia Business Unit (UUS) of PT Bank Sumut for the Period January 2015-December 2019". The purpose of this study is to determine the percentage of the influence of NPF and FDR partially and simultaneously on Profitability (ROA) at the Sharia Business Unit (UUS) of PT Bank Sumut for the period January 2015-December 2019. The data source in this study is secondary data, the type of data in this study is quantitative data collected through documentation techniques. Secondary data is obtained through the balance sheet, productive asset reports and monthly performance of UUS PT Bank Sumut. The sample in this study was 60 (n = 60). The data analysis used is multiple linear regression analysis, simultaneous significance test (F statistical test), partial test (t statistical test) with a significance level of 5% (α = 0.05), correlation coefficient and determination test processed with the help of the SPSS Version 24 application. The results of this study indicate that the Effect of Partial Non-Performing Financing on Profitability (Return On Asset) of UUS PT Bank Sumut for the period January 2015-December 2019 is negative with a weak and significant correlation. The Effect of Partial Finance To Deposit Ratio on Profitability (Return On Asset) of UUS PT Bank Sumut for the period January 2015-December 2019 shows a negative relationship with a moderate and significant correlation. Non Performing Financing (NPF) and Finance To Deposit Ratio (FDR) simultaneously have a moderate and significant positive effect on the Profitability (Return On Assets) of UUS PT Bank Sumut for the period January 2015-December 2019. The ability of the NPF and FDR variables to influence the variation in the increase and decrease of ROA at UUS PT Bank Sumut is 33.1%, while the remaining 66.9% is influenced by other variables not examined in this study.